Improving temozolomide biopharmaceutical properties in glioblastoma multiforme (GBM) treatment using GBM-targeting nanocarriers - Delello Di Filippo, Leonardo [UNESP]; Hofstätter Azambuja, Juliana; Paes Dutra, Jessyca Aparecida [UNESP]; Tavares Luiz, Marcela; Lobato Duarte, Jonatas [UNESP]; Nicoleti, Luiza Ribeiro [UNESP]; Olalla Saad, Sara Teresinha; Chorilli, Marlus [UNESP] (Elsevier, 2021)
Glioblastoma multiforme (GBM) is the most common primary brain cancer. GBM has aggressive development, and the pharmacological treatment remains a challenge due to GBM anatomical characteristics’ (the blood–brain barrier and tumor microenvironment) and the increasing resistance to marketed drugs, such as temozolomide (TMZ), the first-line drug for GBM treatment. Due to physical–chemical properties such as short half-life time and the increasing resistance shown by GBM cells, high doses and repeated administrations are necessary, leading to significant adverse events. This review will discuss the main molecular mechanisms of TMZ resistance and the use of functionalized nanocarriers as an efficient and safe strategy for TMZ delivery. GBM-targeting nanocarriers are an important tool for the treatment of GBM, demonstrating to improve the biopharmaceutical properties of TMZ and repurpose its use in anti-GBM therapy. Technical aspects of nanocarriers will be discussed, and biological models highlighting the advantages and effects of functionalization strategies in TMZ anti-GBM activity. Finally, conclusions regarding the main findings will be made in the context of new perspectives for the treatment of GBM using TMZ as a chemotherapy agent, improving the sensibility and biological anti-tumor effect of TMZ through functionalization strategies.
Keywords: Brain cancer; Cancer therapy; Drug resistance; Functionalization; Glioblastoma; Nanotechnology